Learning Video Based on Contextual Approach Science Content of Grade V Elementary School - Gede Ngurah Griantara Manuaba; DB. KT. NGR. Semara Putra (Indonesian Journal Of Educational Research and Review, 2021)
The lack of use of video media in the learning process causes students to have difficulties in learning. This research aims to develop audiovisual learning media tailored to the needs of today's learning. The test subjects in this study consisted of several experts and students. The experts consist of learning content experts, learning design experts and learning media experts and involve grade V students to conduct individual trials and small group trials. This development research uses ADDIE development model (analyze, design, development, implementation, evaluation) as systematic steps in the product development process. The data collection method in this study consists of observations, questionnaires and interviews. The data analysis techniques used are quantitative and qualitative descriptive data analysis techniques. Based on the results of product trials, the instructional video was declared feasible by the test subjects, namely learning content experts, learning design experts, learning media experts and students. The results of the evaluation of the learning content expert obtained a percentage (95.83%) with very good qualification, the results of the learning design expert's assessment obtained a percentage (94.23%) with very good qualification, the results of the learning media expert's assessment obtained a percentage (85.00%) with good qualifications and the results of student assessments through individual tests obtained a percentage (94.00%) with very good qualification, and the results of student assessments through small group tests obtained a percentage (95.83%). Based on the results of the product trial, it is concluded that the developed learning videos in very good qualifications and suitable for use in the learning process.